2013
DOI: 10.1093/jncimonographs/lgt027
|View full text |Cite
|
Sign up to set email alerts
|

Improving Symptom Communication Through Personal Digital Assistants: The CHAT (Communicating Health Assisted by Technology) Project

Abstract: Mixed findings of the study indicate the need for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…A pilot RCT of 44 patients reported that patients used a handheld device consistently for an average of 10 weeks [35]. Similar results were reported in another pilot RCT of 60 patients that used a PDA for approximately 22 weeks, where 83% of patients completed symptom inventories and 90% watched communication videos when instructed [43]. For the longest study period included in this review (up to six months), Chumbler and colleagues [30] reported that the mean adherence of 48 patients to daily dialogues with a care coordinator was 84%, with a decrease in adherence as treatment progressed.…”
Section: Adherence To Mobile Interventionssupporting
confidence: 62%
See 4 more Smart Citations
“…A pilot RCT of 44 patients reported that patients used a handheld device consistently for an average of 10 weeks [35]. Similar results were reported in another pilot RCT of 60 patients that used a PDA for approximately 22 weeks, where 83% of patients completed symptom inventories and 90% watched communication videos when instructed [43]. For the longest study period included in this review (up to six months), Chumbler and colleagues [30] reported that the mean adherence of 48 patients to daily dialogues with a care coordinator was 84%, with a decrease in adherence as treatment progressed.…”
Section: Adherence To Mobile Interventionssupporting
confidence: 62%
“…In contrast, although one feasibility study reported a non-significant increase in quality of life following a painmonitoring intervention [28], one feasibility study reported no change in wellbeing [39], however both studies had small sample sizes. Negative findings were also reported by Post and colleagues [43] in a pilot RCT study of 60 patients using a PDA device, where patients reported symptoms weekly during treatment periods and viewed videos on how to communicate their symptoms to their clinicians prior to their consultations. This study found that patients' HRQOL were not significantly different between groups.…”
Section: Heath-related Quality Of Life (Hrqol)mentioning
confidence: 77%
See 3 more Smart Citations